HIV risk-related behavior, sexual coercion, and implications for prevention strategies among female fpprentice failors, Ibadan, Nigeria (2002)
We describe a survey of 300 young female apprentice tailors in a periurban community in Ibadan, Nigeria. The objectives were to assess HIV risk-related behavior in order to plan appropriate prevention interventions. Most apprentice tailors were 18-21 years old (68%), single (95%), and had not completed secondary school (98%). History of sexual intercourse was reported by 53 %; 42% had ever experienced unwanted touching of the breast, backside, shoulder, or waist; 4% reported being raped in the last 6 months. Of sexually active women, 57% reported sexual debut with an instructor; 21% had exchanged sex for money or gifts and only 27% had used a condom during their most recent sexual intercourse. Instability of employment and lack of instructor support were primary barriers to implementing a pilot peer education HIV prevention project. The poor social and economic conditions of apprentice tailors make them vulnerable to sexual exploitation and, in turn, to HIV infection. A peer education intervention within the context of a microcredit economic development program may reduce risk for HIV among women in Nigeria's informal economy.